Impact of Investment Decision, Liquidity Management, and Leverage Ratio on the Value of Manufacturing Companies: Investment Decision, Liquidity Management, and Leverage Ratio (Academic Journal of International University of Erbil, 2025)
This study examines how investment decisions, liquidity management, and leverage affect the value of manufacturing companies listed on the Iraqi Stock Exchange from 2019 to 2023. where the independent variables are measured by each of the Total Asset Growth Ratio (TAGR), Net Working Capital Ratio (NWCR), and Debt to Equity Ratio (DTER), versus the dependent variable, which is measured by Price-to-Book Value Ratio (PBVR). Using the audited financial lists of 17 manufacturing companies, purposive sampling was done to obtain the data. A fixed effect model was used to analyze their data's cross-sectional characteristics (PLS) with the help of EViews software 12. The results indicate that the debt-to-equity ratio (DTER) has a significant positive effect on the Price-to-Book Value Ratio (PBVR). However, the Net Working Capital Ratio (NWCR) has a non-significant negative impact on the PBVR. Meanwhile, Total Asset Growth Rate (TAGR) has a significant positive impact on (PBVR). According to the findings of the study, they suggest that manufacturing firms should consider market conditions and industry type when reformulating their annual plans. The financial performance of the company must be evaluated regularly in order to identify potential improvements and responses to possible future problems. Companies should emphasize achieving sustainable growth and increasing corporate value by developing more appropriate investment strategies and understanding how the debt-to-equity ratio (DTER) and total asset growth rate (TAGR) affect PBVR.